2017
DOI: 10.1159/000477611
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography: Employing a Novel Technique for Investigation in Vogt-Koyanagi-Harada Disease

Abstract: Purpose: To report a case of Vogt-Koyanagi-Harada (VKH) disease and describe the imaging findings by means of optical coherence tomography angiography (OCTA). Methods: Medical and ophthalmological history, ophthalmological examination, laboratory evaluation, B-scan ultrasonography, fluorescein and indocyanine angiography, and optical coherence tomography (OCT) were performed at baseline, as well as OCTA. Results: A 50-year-old healthy female presented with decreased vision in both eyes. A Topcon DRI OCT Triton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Of note, these foci correlated with ICGA and decreased in number and size after initiation of therapy [ 15 ]. Similar OCTA findings in VKH have been reported by another case series [ 16 ] and two case reports [ 17 ], [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Of note, these foci correlated with ICGA and decreased in number and size after initiation of therapy [ 15 ]. Similar OCTA findings in VKH have been reported by another case series [ 16 ] and two case reports [ 17 ], [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, SS-OCTA is a better imaging modality tool for detailed chorioretinal angiography than SD-OCTA. Flow voids appear as dark foci in the OCTA CC slab and multiple studies have demonstrated that most FV revealed by OCTA correspond to hypofluorescent spots on ICGA images (19,24,(39)(40)(41)(42) and hyporeflective spots on enhanced-depth imaging (EDI)-OCT (43). Aggarwal et al reported that the CC FV on OCTA images reflected true CC ischemia instead of a shadowing effect from overlying subretinal fluid and RPE detachment as was observed in central serous chorioretinopathy (19).…”
Section: Discussionmentioning
confidence: 99%
“…4,9,10 In addition, CC flow impairments evaluated using OCTA has been reported in eyes with diseases such as age-related macular degeneration (AMD), diabetic retinopathy, central serous chorioretinopathy, retinitis pigmentosa, idiopathic epiretinal membrane, Vogt-Koyanagi-Harada disease, and Alport syndrome. 5,[11][12][13][14][15][16][17][18][19] However, the extent of CC flow impairments reported from different studies have been difficult to compare because different instruments and algorithms have been used to generate and analyze the CC en face flow images and because the capillaries of the CC are beyond the resolution of commercial OCTA instruments so investigators lack the ground truth evidence that they are truly imaging the CC in vivo based on OCTA images. 8-12, 14-17, 20-25 Different terms have been used to evaluate CC flow and flow impairments such as CC vessel flow density (VFD), vessel density (VD), vessel diameter index (VDI), perfusion density (PD), vessel length density (VLD), flow voids (FVs), grey value (GV), signal voids, percent choriocapillaris area of nonperfusion (PCAN), 8,9,[20][21][22][23][24][25][26] but we prefer to use the term flow deficits (FDs), since these areas represent regions of undetectable CC flow when using a particular instrument and algorithm rather than the absolute absence of physiological CC flow, since flow might be detectable under different circumstances.…”
Section: Introductionmentioning
confidence: 99%